2019
DOI: 10.1177/0269881119844188
|View full text |Cite
|
Sign up to set email alerts
|

Role of the galanin N-terminal fragment (1-15) in anhedonia: Involvement of the dopaminergic mesolimbic system

Abstract: Background: Anhedonia is a core feature of depressive disorders. The galanin N-terminal fragment (1-15) plays a role in mood regulation since it induces depression and anxiogenic-like effects in rats. In this study, we analysed galanin N-terminal fragment (1-15) actions in anhedonic-like behaviours in rats using operant and non-operant tests and the areas involved with these effects. Methods: Galanin N-terminal fragment (1-15) effects were analysed in saccharin self-administration, sucrose preference, novelt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 60 publications
3
29
1
Order By: Relevance
“…However, it is important to notice that anhedonia-like behavior, demonstrated e.g., in saccharin self-administration and sucrose preference test after i.c.v. injection of Gal (1-15), was counteracted by the GalR2 antagonist M871 [46]. These results can best be interpreted by assuming that the GalR1-GalR2 heterocomplexes are mainly located on the GABA VTA interneurons innervating the VTA DA neurons.…”
Section: Figurementioning
confidence: 92%
See 4 more Smart Citations
“…However, it is important to notice that anhedonia-like behavior, demonstrated e.g., in saccharin self-administration and sucrose preference test after i.c.v. injection of Gal (1-15), was counteracted by the GalR2 antagonist M871 [46]. These results can best be interpreted by assuming that the GalR1-GalR2 heterocomplexes are mainly located on the GABA VTA interneurons innervating the VTA DA neurons.…”
Section: Figurementioning
confidence: 92%
“…As to a leading role of GalR2 vs. the GalR1 protomer in this regulation of the VTA DA neurons, it was found that Gal (1-15) reduced the mRNA expression of the DA transporter and vesicular monoamine transporter 2 that also reflect an increased GABA inhibition of the VTA DA neurons. Instead, there was a significant increase in the mRNA expression of D3R in the VTA by Gal (1-15) which can be explained by the fact that the D3R can operate mainly as an auto-receptor in VTA [46]. The results are compatible with the view that the VTA GalR2 protomer upon activation by Gal (1-15) induced an activation of the GABA interneurons causing inhibition of the VTA DA neurons leading to anhedonia-like behavior and a neurochemical down regulation of the meso-limbic DA reward neurons [46].…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations